Determinants of population knowledge and attitudes towards population education among Nepalese secondary teachers - Krishna, Ranjit Bal 1959- (College of Education, University of the Philippines Diliman, 1998)
This descriptive research study was designed to identify the determinants of population knowledge and attitude of secondary teachers towards population education and to investigate the differences existing in knowledge and attitude towards population education among untrained and trained secondary teachers in selected schools of Kathmandu Valley of Nepal. It hypothesized that (a) nine demographic characteristics of background variables of the teachers are the determinants of population knowledge and attitudes of secondary teachers, viz., sex, marital status, age, education, teaching experience, population training, population teaching experience, and exposure to other sources of information on population education such as TV and other training; and that (b) significant differences exist in the population knowledge and attitude towards population education among untrained and trained secondary teachers. The research was undertaken in Kathmandu, Lalitpur and Bhaktapur districts of Kathmandu Valley in the Central Development Region of Nepal. The sample of 300 secondary teachers randomly selected from 114 secondary schools included 227 males and 73 females. Of the 300 teachers, 150 were trained in population education and 150 were untrained. The main data gathering instruments was a three part-questionnaires elicited background information on the teacher-respondents (part I), determined the teachers' population knowledge through a 50 -item multiple choice knowledge test (part II), and gathered data on teachers' attitudes towards population education using a 25 -item attitude inventory of the Likert-scale type (part III). The instrument was developed based on a table of specifications which was in turn based on the secondary population education curriculum in Nepal and covering all the five major content areas of population education: Demography and population education, Determinants of population change, Consequences of population growth, Human sexuality and reproduction, and Planning for the future and population related matters. Frequency distribution, means, standard deviation, t-test, and multiple regression analysis were used to analyze data. The major findings of the study are (1) population training and population teaching experience were found to be prominent determinants of population knowledge of secondary teachers. Sex, age, marital status educational attainment, teaching experience, and exposure to TV and other training were not considered as determinants of teacher's knowledge about population education; (2) the teachers' knowledge about population education differed significantly by eight background variables, namely sex (male), age (21-30 years), marital status (married respondents), education (Bachelor's degree), teaching experience (0-10 years), population training (trained teachers), population teaching experience (<5 years), and exposure to TV (teachers with exposure to TV); (3) all the background variables included in the present study were not proved to be determinants of teacher's attitude towards population education; and (4) teachers' attitude towards population education differed significantly with age, educational attainment, teaching experience and exposure to other training. The researcher recommended several measures to improve the secondary population education curriculum in Nepal such as: 1. give greater emphasis in information on demographic aspects of population education; 2. review the curriculum and resource materials of teacher training programme on population education; 3. improve the training strategies and modules for different groups of teachers in accordance with their age groups and years of teaching experience; 4. encourage the participation of female teachers; 5. lengthen the duration of teachers' training programmes; 6. utilize and produce more supplementary/instructional materials, modules and teacher's guide and manuals; 7. incorporate new concepts of population related matters in the materials given to teachers during training; 8. emphasize and reinforce the attitudes of teachers towards population education; 9. stress value clarification; 10. organize more training programmes of different types for different groups of teachers; and 11. direct training programme at priority target groups identified by the present study. Further research is also recommended on the identification of other possible background variables as determinants of teacher's knowledge and attitude towards population education; sustainability of population education programme; incorporation of population curriculum in to all teacher's in population education; organization of a nation-wide multi-sectoral campaign on population issues through secondary teachers for public awareness; and evaluation and monitoring of population education training programme.